Sustainable Production of Drinking Water Company (Study at Pt. X, Cilegon, Banten Province) - Whasf Velasufah (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
This study provides recommendations for the sustainability of drinking water production at PT X. The methods used include laboratory analysis, surveys, NVP, BCR, and analytical hierarchy process (AHP) analysis. The Results shows that the water quality of PT X complies with the quality standards set in SNI 3553 of 2015 concerning Mineral Water. With a raw water source discharge of 1.375 m³/second, PT X can meet its annual needs in just about 2 hours and 38 minutes. The production of drinking water by PT X is also economically viable, as the benefits generated exceed the costs incurred. This is supported by a Benefit-Cost Ratio (BCR) of 2,23 and a Net Present Value (NPV) of Rp 63.704.481.792,19. Furthermore, based on the Analytical Hierarchy Process (AHP) analysis, the main priority for sustainable drinking water production is to enhance environmentally friendly production processes, with a weight of 0,34 among all alternatives. For sustainable drinking water production criteria, the first priority is water quality with a weight of 0,314, followed by social acceptance with a weight of 0,290, and economic value at 0,289. In conclusion, this research provides strategic recommendations for maintaining sustainable drinking water production that is environmentally friendly, economical, and socially accepted at PT X.